Aliyev , Cavid - (:unkn) unknown (My University, 2026)
Cavid Gulmirza Aliyev graduated from the Azerbaijan State University of Arts named after M. Aliyev, where he studied from 1990 to 1996. Since 2000, he has been a faculty member of the Department of Fundamentals of Architecture, Faculty of Architecture, at Azerbaijan University of Architecture and Construction. His research focuses on architectural issues and theory. He is the author of numerous scientific publications and academic curricula.